1996
DOI: 10.1038/382250a0
|View full text |Cite
|
Sign up to set email alerts
|

Role of leptin in the neuroendocrine response to fasting

Abstract: A total deficiency in or resistance to the protein leptin causes severe obesity. As leptin levels rise with increasing adiposity in rodents and man, it is proposed to act as a negative feedback 'adipostatic signal' to brain centres controlling energy homeostasis, limiting obesity in times of nutritional abundance. Starvation is also a threat to homeostasis that triggers adaptive responses, but whether leptin plays a role in the physiology of starvation is unknown. Leptin concentration falls during starvation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

140
2,063
15
91

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,893 publications
(2,309 citation statements)
references
References 22 publications
140
2,063
15
91
Order By: Relevance
“…23 Jeff Flier and colleagues at the Beth Israel Hospital in Boston were the first to elegantly show that leptin was most likely to have evolved as a signal for Inheritance and human obesity S O'Rahilly and IS Farooqi starvation rather than nutrient excess, in that the rapid fall of leptin in the plasma seen upon fasting was necessary for the normal neurohormonal adaptations seen with starvation in mammals. 24 Mutations in single genes involved in the central control of energy balance can lead to human obesity At this stage in the mid-1990s, the relevance of leptin to human physiology was uncertain. As humans gain fat mass, in general the levels of leptin increase, 25 and this suggested that either leptin resistance was a major factor in human obesity or indeed that leptin was irrelevant to the control of human body weight.…”
Section: Discussionmentioning
confidence: 99%
“…23 Jeff Flier and colleagues at the Beth Israel Hospital in Boston were the first to elegantly show that leptin was most likely to have evolved as a signal for Inheritance and human obesity S O'Rahilly and IS Farooqi starvation rather than nutrient excess, in that the rapid fall of leptin in the plasma seen upon fasting was necessary for the normal neurohormonal adaptations seen with starvation in mammals. 24 Mutations in single genes involved in the central control of energy balance can lead to human obesity At this stage in the mid-1990s, the relevance of leptin to human physiology was uncertain. As humans gain fat mass, in general the levels of leptin increase, 25 and this suggested that either leptin resistance was a major factor in human obesity or indeed that leptin was irrelevant to the control of human body weight.…”
Section: Discussionmentioning
confidence: 99%
“…17,38,39 In rodents, leptin modulates thyroid hormone production in situations in which energy conservation through a reduction in metabolic rate is required. 40 Such effect appears to occur principally at the level of TRH neurons in the paraventricular hypothalamic nucleus (PVN). Leptin could act directly at receptors on the TRH neuron or indirectly through other hypothalamic neurons that project to the PVN.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well characterised that in states of negative energy balance, such as prolonged fasting, regulation of the HPT axis is altered, as manifested by low plasma T3, and T4, with a low or inappropriately normal TSH and a reduction in TRH biosynthesis and secretion [1,5,9,15,16,25,27,33,51,64]. This central hypothyroidism following starvation may be an important adaptive response, by reducing thermogenesis and hence, reducing the obligatory use of energy stores [21].…”
Section: The Hpt Axis and Starvationmentioning
confidence: 99%